Diagnosis and non‐surgical treatment of peri‐implant diseases and maintenance care of patients with dental implants – Consensus report of working group 3. (3rd September 2019) - Renvert, Stefan; Hirooka, Hideaki; Polyzois, Ioannis; Kelekis‐Cholakis, Anastasia; Wang, Hom‐Lay; ,
Abstract: The following consensus report is based on four background reviews. The frequency of maintenance visits is based on patient risk indicators, homecare compliance and prosthetic design. Generally, a 6‐month visit interval or shorter is preferred. At these visits, peri‐implant probing, assessment of bleeding on probing and, if warranted, a radiographic examination is performed. Diagnosis of peri‐implant mucositis requires: (i) bleeding or suppuration on gentle probing with or without increased probing depth compared with previous examinations; and (ii) no bone loss beyond crestal bone level changes resulting from initial bone remodelling. Diagnosis of peri‐implantitis requires: (i) bleeding and/or suppuration on gentle probing; (ii) an increased probing depth compared with previous examinations; and (iii) bone loss beyond crestal bone level changes resulting from initial bone remodelling. If diagnosis of disease is established, the inflammation should be resolved. Non‐surgical therapy is always the first choice. Access and motivation for optimal oral hygiene are key. The patient should have a course of mechanical therapy and, if a smoker, be encouraged not to smoke. Non‐surgical mechanical therapy and oral hygiene reinforcement are useful in treating peri‐implant mucositis. Power‐driven subgingival air‐polishing devices, Er: YAG lasers, metal curettes or ultrasonic curettes with or without plastic sleeves can be used to treat peri‐implantitis. Such treatment usually provides clinical improvements such as reduced bleeding tendency, and in some cases a pocket‐depth reduction of ≤ 1 mm. In advanced cases, however, complete resolution of the disease is unlikely.